VALIDITAS PERANGKAT PEMBELAJARAN DALAM MODEL PEMBELAJARAN DALIHAN UNTUK MELATIH KETERAMPILAN BERPIKIR KREATIF SISWA - Guna Ria Siagian; Festiyed Festiyed (Jurnal Muara Pendidikan, 2023)
This research aims to validate learning tools in RPP, LKPD and creative thinking tests by utilizing the DALIHAN learning model on Biodiversity material at Pematang Siantar Methodist High School. The survey results show that the nature of the items to be submitted, seen from the validity of the lesson plan, meets the very valid rules with a validator value of between 80 to 100%, the LKPD is very valid, and the legitimacy of the validator increases from the validator value of between 80 to 92% and the creative thinking test meets the following steps. It is a valid measure with values ranging from 80% to 92%. According to this research, it can be concluded that learning tools that use the DALIHAN model in Biodiversity material are valid for training students' creative thinking skills and are suitable for use as learning models in schools.